2009
DOI: 10.1108/00070700910992844
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported and observed behavior of primary meal preparers and adolescents during preparation of frozen, uncooked, breaded chicken products

Abstract: PurposeThe purpose of the present study was to observe the preparation practices of both adult and young consumers using frozen, uncooked, breaded chicken products, which were previously involved in outbreaks linked to consumer mishandling. The study also sought to observe behaviors of adolescents as home food preparers. Finally, the study aimed to compare food handler behaviors with those prescribed on product labels.Design/methodology/approachThe study sought, through video observation and self‐report survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…As observational studies suggest, knowledge and self-reported behavior do not necessarily reflect the actual behavior (Behrens et al, 2010;Byrd-Bredbenner, Berning, Martin-Biggers, & Quick, 2013;Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;DeDonder et al, 2009;Dharod et al, 2007;Fein, Lando, Levy, Teisl, & Noblet, 2011;Hoelzl et al 2013;Kindall et al, 2004;Phang & Bruhn, 2011;Worsfold & Griffith, 1997). However, an insight into what consumers know and what they need to be educated about can be obtained by such reported behavior .…”
Section: Introductionmentioning
confidence: 85%
“…As observational studies suggest, knowledge and self-reported behavior do not necessarily reflect the actual behavior (Behrens et al, 2010;Byrd-Bredbenner, Berning, Martin-Biggers, & Quick, 2013;Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;DeDonder et al, 2009;Dharod et al, 2007;Fein, Lando, Levy, Teisl, & Noblet, 2011;Hoelzl et al 2013;Kindall et al, 2004;Phang & Bruhn, 2011;Worsfold & Griffith, 1997). However, an insight into what consumers know and what they need to be educated about can be obtained by such reported behavior .…”
Section: Introductionmentioning
confidence: 85%
“…Other similar studies evaluated the ease of how different microorganisms can be transferred to food by different consumer handling scenarios (Barker, Naeeni, & Bloomfield, 2003;Haysom & Sharp, 2005;Redmond et al, 2004). A limited number of studies about bacterial transfer between surfaces (Deboer & Hahne, 1990;Humphrey, Martin, & Whitehead, 1994) have also been conducted. A significant discrepancy in the reported values of transfer rate from a donor to recipient was reported in the literature, and this confirms that the transfer rate is a big challenge.…”
Section: Bacterial Transfermentioning
confidence: 97%
“…In the U.S., 5e57% of those surveyed neglected to wash their hands or did not wash their hands correctly, and 13e71% used improper crosscontamination procedures (DeDonder et al, 2009;Kendall et al, 2004;Redmond & Griffith, 2003b). Only 45% tried to wash their hands before preparing a meal and only 84% of those used soap (Anderson et al, 2004).…”
Section: Observational Consumers Practicementioning
confidence: 98%
See 1 more Smart Citation
“…It appears that consumers either knew about this recommendation or have other reasons for putting food away quickly. Future studies should investigate if actual practice times are similar to the reported practice times as research has shown self-reported practices to be less precise than practices observed (27).…”
Section: Preparation and Storage Behaviormentioning
confidence: 99%